The Dominicans in the Americas and the Philippines (c. 1500-c. 1820)
1 online resource.
Keywords: "The Dominicans in the Americas and the Philippines (c. 1500-c. 1820) is part of a renewal of interest in the global history of the Dominican Order. Many of the essays were carefully selected among some of the papers presented at the III International Conference on the History of the Order of Preachers in the Americas, a gathering that stands in continuity with the conferences of Mexico (2013) and Bogotá (2016). This book, the contributors of which are active researchers specializing in the history of the Order of Preachers in Latin America, is organized in four parts: Women and the Order of Preachers; "Benditos Bienes": Libraries and Material Patrimony; Missions, Devotional and Daily Life; The Order of Preachers and their Writings. Contributions deal with different subfields including art history, gender studies, history of the book, and intellectual history more broadly. Additionally, it contains a chapter examining the historiography of the Order of Preacher's in Latin America. Covering the time range from 1510 to the early nineteenth century, the book fills a gap in the historiography of the Order of Preachers in the Americas, especially in English-language scholarly literature. Students of Latin American history, history of Christianity, and the history of global Catholicism will surely find the volume to be of great interest"--